Soviet diplomats and Comintern representatives in People’s Republic of Tuva in the 1920s - Mollerov, Nikolay M. (The New Research of Tuva, 2016)
This is the first study of the role Soviet diplomats and representatives of the Communist International (Comintern) played in the Soviet-Tuvan relations during the first decade after the emergence of the young Tuvan state – People’s Republic of Tuva (1920s). From representing the interests of a small military mission, the Soviet diplomatic office in Tuva evolved into a full-scale embassy of the Soviet state. Its history clearly falls into two stages: from early 1920s to 1927 Soviet mission members largely abstained from interfering into PRT’s internal issues, but subsequently they started actively promoting the left wing of Tuvan People Revolutionary Party, which contributed to its accession to power.The Soviet state began to act as PRT’s patron on the international arena. This policy of support and custody was in accordance with Article 2 of PRT’s constitution. Using documentary sources, this article traces the appointments and transfers of a number of Soviet diplomatic officers and consuls (F.G. Falsky (Falkovsky), I.A. Chichayev, F.F. Razumov, A.G. Starkov), as well as Comintern representatives (I.G. Safyanov, B. Tsivenzhapov, V. Borovikov, A.M. Amur-Sanan, S.A. Natsov, V. Machavariani, V.A. Bogdanov). In the duopoly of consuls and Comintern representatives, the former dominated at the earlier stages, but after the defeat of Chinese communists in 1927 the Soviet leaders thought that Socialist transformations in Mongolia in Tuva should be sped up.The article makes use of archival sources from the State Archive of the Republic of Tuva, Russian State Archive of Socio-Political History (RGASPI), and the Research archive of Tuva Institute for Humanities and Applied Socioeconomic Studies.
Keywords: People’s Republic of Tuva (PRT); Soviet consulate; USSR’s envoy plenipotentiary in PRT; history of Tuva; Comintern in Tuva; consulates in Tuva